Large-scale school scoliosis screening in a multi-ethnic, high-altitude region of southwestern China: an epidemiological study of 69,811 children and adolescents - Song, Shanshan; He, Ying; Zhen, Qing; Shui, Tiejun; An, Weiwei; Dai, Limei; Tan, Min; Hao, Jiaxin; Song, Ruifang; Shen, Yong; Yan, Xiangyu; Chang, Litao (Frontiers in Public Health, 2025)
ObjectivesTo establish the first large-scale epidemiological profile of scoliosis among children and adolescents in Yunnan, China, and identify key demographic, anthropometric, and geographic determinants in this multi-ethnic, high-altitude region.Study designA population-based cross-sectional screening survey using multistage stratified cluster sampling.MethodsA population-based cross-sectional survey of 69,811 students aged 6–18 was conducted in 2021 using multistage stratified cluster sampling across Yunnan, which included demographic information (gender, ethnicity, grade), anthropometric measurements (height, weight), and scoliosis outcomes (presence and severity assessed via scoliometer-based Angle of Trunk Rotation). Regional covariates (altitude, economic status) were also incorporated. Multi-factor regression analysis identified risk factors.ResultsInitial screening identified 1,379 scoliosis cases, yielding an overall detection rate of 1.98%. The rate was significantly higher in females than in males (2.4% vs. 1.6%, p < 0.001), with males showing higher rates at ages 14 and 16, and females exhibiting consistently higher detection during early and mid-adolescence and a peak at age 17 (3.7%). The detection rate also increased progressively with education level (primary school: 1.0%; middle school: 2.7%; high school: 3.3%). Multivariable regression analysis indicated that scoliosis risk was positively associated with female sex (AOR = 1.738, 95% CI: 1.546–1.954), higher education levels (middle school: AOR = 1.703, 95% CI: 1.408–2.059; high school: AOR = 1.891, 95% CI: 1.534–2.331), and greater height (per cm AOR = 1.060, 95% CI: 1.052–1.069). Protective factors included rural residence (AOR = 0.717, 95% CI: 0.638–0.805), minority ethnicity (AOR = 0.856, 95% CI: 0.760–0.964), moderate (AOR = 0.515, 95% CI: 0.452–0.586) or low GDP (AOR = 0.067, 95% CI: 0.044–0.104), medium (AOR = 0.075, 95% CI: 0.049–0.116) or high altitude (AOR = 0.098, 95% CI: 0.068–0.140), and greater weight (AOR = 0.955, 95% CI: 0.947–0.962).ConclusionThe elevated detection rate in Yunnan highlights the influence of regional sociodemographic and environmental factors. Findings support tailored screening strategies, particularly for urban female adolescents and minority populations in high-altitude areas.